Experiences using google translate application for translation used by English department students - Nurul Iftitah; Rahayu Kuswardani (Journal of Research on English and Language Learning (J-REaLL), 2022)
This study exposed experiences using Google translate application for translation used by English Department students. This research is focused on explaining problems and strategies using Google Translate used by English Department students. This research used a descriptive qualitative design. Researchers selected 20 students from English Department who had taken translation subject and agreed participated in this research. The instrument used was a questionnaire in the form of open-ended questions where students had to express their answers in a paragraph. In the questionnaire there were instructions and a descriptive text about tourism places written in Indonesian that must be translated into English by students using two ways. First, students used Google translate application. Second, students translated those texts manually without an application. There were eight questions about what translation problems they found after using the app and what strategies they did to fix the result. Several points were found to be improved in the process of translation using Google translate, including to deal with grammatical error, to deal with inappropriate words or phrases, to deal with no provided meaning in google translate and to deal with abbreviation existed in Indonesian language and to deal with word for word translation.